REKRUTMEN PEGAWAI NEGERI SIPIL DI BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI SELATAN - Rachman, Erick Fathur; Mappamiring, Mappamiring; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study is to find out the recruitment of Civil Servants in the Regional Personnel Agency of South Sulawesi Province. This study uses qualitative methods to describe and explain the recruitment of Civil Servants. Data collection techniques in this study were interviews, observation and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion drawing. The results of this study can be seen that the Regional Personnel Board of South Sulawesi Province is the coordinator in the process of organizing the selection of Civil Servants in the scope of the South Sulawesi Provincial Government. It is known that in the implementation of the recruitment of Civil Servants at the Civil Service Agency of South Sulawesi Province, there are 4 important stages, namely: Planning for employee needs, Position Analysis, Formation and Procurement of employees. In the process of implementing the recruitment, it is known that there are still various problems starting from the allocation of personnel budgets, regional financial capabilities, to the lack of information regarding a tentative selection schedule.Keywords: Recruitment, Civil Servants.